A LEADERSHIP MODEL FOR EFFECTIVE INTERNATIONALIZATION STRATEGIES IN THAI HIGHER EDUCATION INSTITUTIONS - SINJUMPASAK, PATTAMA; MHUNPIEW, NATHARA (Scholar: Human Sciences, 2022)
This study aimed to develop a leadership model for effective internationalization (IZN) strategies in Thai higher education institutions (HEIs). The study was based on three objectives: 1) To explore the leadership factors for internationalization strategies in the global higher education institutions, 2) To validate a proposed leadership model for effective internationalization strategies in Thai higher education institutions, and 3) To verify a leadership model for effective internationalization strategies in Thai higher education institutions. The mixed methods used for this study included documentary review, semi-structured interviews, expert validation, and questionnaire. A proposed leadership model for effective IZN strategies in Thai HEIs was validated by 21 experts; as well as it was verified by the statistical analysis of the results from the questionnaire survey on leadership factors and IZN strategies in two Thai private universities. The findings have shown that five leadership factors and 15 IZN strategies, which were validated by the experts in terms of suitability, could be apply to Thai HEIs. In addition, other three components, comprising institutional vision, context and policy and priority, are needed for successful implementation of IZN. Besides, the results from verifying the model reflect that all leadership factors have significantly influence on this leadership model. Since leadership in HEIs plays a very crucial role in enhancing effective IZN strategies to achieve their IZN goals. It is recommended that HEIs could use this study as an idea for developing their leadership model for successful IZN strategies that fit to their vision, contexts, and priority.